Rhythmic motion in selected chorale preludes from J. S. Bach's "Orgelbuechlein". - Francis, Kelly Anne. (University of Ottawa (Canada), 2001)
This thesis investigates rhythmic motion in-selected chorale preludes from J. S. Bach's Orgelbuchlein collection. It examines how layers of motion, produced from the contrapuntal layering of voices, interact within each selected chorale prelude. It shows how layers of motion either align and produce synchronous rhythmic motion or misalign and produce non-synchronous rhythmic motion. In particular, this thesis investigates how alternations between synchronous and non-synchronous layers of motion correspond to and articulate both phrase form and tonal structure in these works.
Keywords: Music.